The Influence of Learning Motivation on Students' Mathematical Communication Skills - Tiara Tiara Lisdianti Susanti H; Mimih Aminah (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Mathematical communication skills are a fundamental component of mathematics learning because they enable students to express ideas, reasoning, and problem-solving processes clearly both orally and in writing. However, many junior high school students still show limitations in articulating mathematical concepts, and their level of learning motivation may influence this. This study aims to analyze the relationship between learning motivation and mathematical communication skills among eighth-grade students at SMPN 5 Sumedang. The research employed a quantitative approach with an experimental design. The subjects were 34 students from classes VIII-H and VIII-I, selected through cluster sampling. Learning motivation was treated as the independent variable, while mathematical communication skills were the dependent variable. Data were collected using two instruments: a Likert-scale learning motivation questionnaire and an essay test on exponents to measure mathematical communication skills. Data analysis involved descriptive statistics and Product-Moment correlation after satisfying the assumptions of normality and linearity. The results indicated that students' learning motivation was in the moderate category (mean = 77.33), as were their mathematical communication skills (mean = 71.77). Correlation analysis yielded r = 0.305, indicating a positive but weak relationship between the two variables, which was not statistically significant at the 0.05 level. These findings suggest that although learning motivation tends to be associated with mathematical communication skills, it is not a dominant factor. Therefore, efforts to improve students' mathematical communication should also consider other aspects such as instructional strategies, student engagement, and a supportive learning environment.